Formation and dynamics of vegetated fluvial landforms follow the biogeomorphological succession model in a channelized river. Issue 9 (13th April 2020) - Corenblit, Dov; Vautier, Franck; González, Eduardo; Steiger, Johannes
Abstract: Feedback between hydrogeomorphological processes and riparian plants drives landscape dynamics and vegetation succession in river corridors. We describe the consequences of biogeomorphological feedback on the formation and dynamics of vegetated fluvial landforms based on observations from the channelized Isère River in France. The channel was laterally confined with embankments and mostly straightened. From the beginning of the 1970s to the end of the 1990s, alternate bars were progressively but heavily colonized by vegetation. This context presented an exceptional opportunity to analyse temporal adjustments between fluvial landforms and vegetation succession from bare gravel bars to mature upland forest as the consequence of biogeomorphological interactions. Based on a GIS analysis of aerial photographs (between 1948 and 1996), we show that the spatiotemporal organization of vegetated bars within the river channel observed in 1996 resulted from a bioconstruction and biostabilization effect of vegetation and interactions between bars of varying age, size and mobility. Field measurements in 1996 reflected how a strong positive feedback between sedimentary dynamics and riparian vegetation succession resulted in the construction of the vegetated bars. A highly significant statistical association of geomorphological and vegetation variables (RV of co‐inertia analysis = 0.41, p < 0.001) explained 95% of the variability in just one axis, supporting the existence of very strong feedback between geomorphological changes (i.e. the transformation of small bare alternate bars to fluvial landforms covered by mature upland forest, and vegetation succession). Such dynamics reflect the fluvial biogeomorphological successions model, as described by the authors earlier. © 2020 John Wiley & Sons, Ltd. Abstract : We describe the biogeomorphological consequences of interactions between riparian vegetation and fluvial dynamics on the channelized Isère River, France. We show that the spatiotemporal organization of vegetated bars results from a strong bioconstruction and biostabilization effect of vegetation. A highly significant statistical association between the variation in geomorphological characteristics and vegetation succession supports the existence of strong biogeomorphological feedback.